Identification of Salmonella spp. Contamination in Gado-Gado Sold Around the Tadulako University Campus - Pebi Angreni; I Nengah Kundera; Yulia Windarsih; Mohammad Jamhari; Vita Indri Febriani; Abdul Ashari (Biology, Medicine, & Natural Product Chemistry, 2026)
Salmonella spp. are Gram-negative rod-shaped bacteria commonly found in the gastrointestinal tract of humans and animals and are recognized as one of the major causes of foodborne diseases. This study aimed to identify the presence of Salmonella spp. in gado-gado sold in the canteens of Tadulako University. This research employed a descriptive exploratory laboratory design. Samples were collected from five different canteens using a random sampling technique. Microbiological analyses were conducted through presumptive and confirmatory tests using the Most Probable Number (MPN) method, Total Plate Count (TPC), Gram staining, cultivation on selective Salmonella–Shigella Agar (SSA), and biochemical testing using Triple Sugar Iron Agar (TSIA). The MPN results showed an average value of 4,900 MPN/mL of sample, while the TPC reached 35,800/ml sample. These values indicate that the food product does not meet the microbiological safety standards established by the Indonesian Ministry of Health, as the TPC exceeds the maximum permissible limit of 104 CFU/mL.